Polyhydroxyalkanoates (PHA) production from palm oil mill effluent (POME) using mixed culture in sequencing batch reactor (SBR) - Zainal Abideen, Muzaaffar; Ahmad, Mohd. Azlan; Razak, Rohani; Md. Din, Mohd. Fadhil; Ujang, Zaini; Loosdrecht, M.C.M. Van; Ismail, Mohd. Nasir; Husin, Aishah (Faculty of Civil Engineering, 2006)
Polyhydroxyalkanoates (PHAs) are raw materials for production of biodegradable plastics, generated by a range of microbes, cultured under different nutrients and experimental conditions. PHAs usually lipid in nature, are accumulated as storage materials in the form of mobile, amorphous, and liquid granules. Currently, the main limitation for PHAs production is cost of production. Biodegradable plastics from renewable resources, such as PHAs, are alternative to petroleum-based plastic materials, which are non-biodegradable. The aim of this study was to develop a biological process to produce PHAs from palm oil mill effluent (POME). A fed-batch was utilized for fifteen months for POME particularly to optimize the PHAs production under various experimental conditions. The POME cultivation was studied under six experimental conditions, such as COD:N:P ratios, HRT=SRT, air flowrates, substrates feeding rates, anoxic/aerobic and microaerophilic-aerobic. The production rate of PHAs under feast-famine regime occurred rapidly between three to four hours during the substrate uptake rate. The results showed that a short chain fatty aci(especially acetic acid) from POME was considered the most optimum carbon source for PHAs production in the study. The optimum experimental condition for high PHAs production from POME recorded in the cycling of microaerophilic-aerobic experiments with a combination of COD/N:COD/P ratio (490:200 g/g), long retention time (6 to 10 h) and slow feeding rate (20 ml/min). This study showed that the increased of PHAs production would not necessarily enhance the removal of total organic carbon (TOC), phosphate (PO4-P) and nitrate (NO3-N). TOC removal was recorded at range 18 to 33%, while PO4-P and NO3-N removal did not show any consistent trend. A statistical design of experiment was conducted to optimize the PHAs production and organic removal (TOC, PO4-P and NO3-N). Results from response surface method (RSM) analysis, both COD/N:COD/P ratio and air flowrate showed significant influence on PHAs production, TOC, and NO3-N removal. It can be concluded that the PHAs storage capacity was higher two to three times in aerobic compared to anoxic conditions.